Connectivity Results of Hierarchical Cubic Networks as Associated with Linearly Many Faults - Cheng, Eddie; Ke Qiu; Zhizhang Shen (2014 IEEE 17th International Conference on Computational Science and Engineering, 2014)
We establish a general fault-tolerance property for the interesting hierarchical cubic networks, when a linear number of vertices are removed from such a network. As its application, we discuss and derive several connectivity results of its underlying graph, including its restricted connectivity, cyclic vertex-connectivity, component connectivity, and conditional diagnosability. These results demonstrate several fault-tolerance properties of the hierarchical cubic networks.